Charlie Bone and the time twister - Nimmo, Jenny (New York : Orchard Books, 2003)
Back at Bloor's Academy after Christmas vacation, Charlie finds himself confronted with a new problem when young Henry Yewbeam, who vanished during a game of marbles in 1916, suddenly appears and needs help to find his family.
Keywords: Magic -- Juvenile fiction; Schools -- Juvenile fiction; Boarding schools -- Fiction; Magic -- Fiction; Schools -- Fiction; Time travel -- Fiction; England -- Juvenile fiction; England -- Fiction; Fantastic fiction; Children's stories